The Historical Aspects of Economic and Legal International Relations of Independent Kazakhstan and China (1991-1997) - KARASAYEV, Gani M.; YENSENOV, Kanat A.; ZHUMAGULOV, Bolat S.; ALDABERGENOV, Kurykbay M.; BATKEEVA, Bakhit T. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
The first ten years of Independence of Kazakhstan have undergone the events in many parts of the world especially as a result of collapse of Soviet Union in 1991 major changes happened in the geopolitical map of Central Asia. The interest of the United States, the European Union, China and other world powers to the new independent Central Asian republics has risen day by day. The reason of this situation is that the deepening of the political situation in the republic, the complexity of interethnic relations, and instability in the economy in the first period attracted attention of the world's leading states. As a result of bilateral efforts, one can state that these days there is unsolved problem between Kazakhstan and the People's Republic of China. In particular, the frontier between the two countries has been fully defined and turned to the place of friendship and cooperation. The People's Republic of China welcomes all the initiatives and proposals of Kazakhstan on the international arena. Both sides are active members of the SCO. In all areas of communication, there is also a great deal of comprehension and appreciation. The range of economic integration is expanding and the volume of trade relations increases annually. The article informs about initiatives and results of relations between Kazakhstan and the People's Republic of China in the 90s of the XX century through the scientific data.